Colonial Kinship : Guaraní, Spaniards, and Africans in Paraguay - Austin, Shawn Michael (Book collections on Project MUSE., 2020)
"In Colonial Kinship: Guaraní, Spaniards, and Africans in Paraguay, historian Shawn Michael Austin traces the history of conquest and colonization in Paraguay during the sixteenth and seventeenth centuries. Emphasizing the social and cultural agency of Guaraní-the indigenous people of Paraguay-not only in Jesuit missions but also in colonial settlements and Indian pueblos scattered in and around the Spanish city of Asunción, Austin argues that interethnic relations and cultural change in Paraguay can only be properly understood through the Guaraní logic of kinship. In the colonial backwater of Paraguay, conquistadors were forced to marry into Guaraní families in order to acquire indigenous tributaries, thereby becoming "brothers-in-law" (tovajaÌ) to Guaraní chieftains. This pattern of interethnic exchange infused colonial relations and institutions with Guaraní social meanings and expectations of reciprocity that forever changed Spaniards, African slaves, and their descendants. Austin demonstrates that Guaraní of diverse social and political positions actively shaped colonial society along indigenous lines"--